The Effect Of Perceived Usefulness, Perceived Ease Of Use, Perceived Deception On Intention To Continue Use With Trust And Perceived Risk As Mediation Variables Brimo Application Users In Indonesia - Alfira Dinda Aprilliana; Yuliana, Ade; Prasetyo, Agung (Universitas Muhammadiyah Pontianak, 2026)
This study investigates determinants of continuance intention to use mobile banking, focusing on perceived usefulness, perceived ease of use, and perceived deception, with trust and perceived risk as mediators. Integrating the Technology Acceptance Model (TAM) and Expectation Confirmation Theory (ECT), data from 210 BRImo users in Indonesia were analyzed using PLS-SEM. Findings show that perceived usefulness enhances trust and continuance intention, while perceived ease of use reduces perceived risk. Perceived deception increases risk and weakens trust. Trust has no significant direct effect on continuance intention, whereas perceived risk negatively affects it. The study extends TAM by incorporating deception in post-adoption behavior. Keywords: Perceived Usefulness; Perceived Ease Of Use; Perceived Deception; Trust, Perceived Risk; Intention to Continue Use; Mobile Banking